Intraosseous Hemangioma of the Inferior Turbinate - Kazuya Takeda; Yukinori Takenaka; Michiko Hashimoto (Case Reports in Medicine, 2010)
The nasal cavity harbors an enormous variety of neoplasms, including epithelial and mesenchymal tumors. Hemangioma is an infrequent mesenchymal tumor of the nasal cavity, mostly arising in the mucosa and rarely in the bones. We describe the case of a 73-year-old woman who was referred to our hospital with a tumor in her left nasal cavity. The tumor originated from the left inferior turbinate. Histological examination subsequent to complete excision revealed that the tumor was an intraosseous cavernous hemangioma. To our knowledge, this is the second case of intraosseous hemangioma of the inferior turbinate reported in the English literature.